Daredevil - Milchan, Arnon; Foster, Gary.; Arad, Avi.; Johnson, Mark Steven, 1966-; Affleck, Ben, 1972-; Garner, Jennifer, 1973-; Duncan, Michael Clarke; Farrell, Colin, 1976-; Twentieth Century-Fox Film Corporation; Regency Enterprises; Marvel Enterprises; New Regency (Firm); et al. ([United States] : 20th Century Fox Home Entertainment, 2003)
By day, blind attorney Matt Mudock toils for justice in Hell's Kitchen. By night, he's Daredevil, a man without fear. He's a masked vigilante stalking the dark streets with an uncanny "radar sense" that allows him to see with superhuman capabilities. When the love of his life is targeted by New York City's ruthless Kingpin and his deadly assassin, Bullseye, Daredevil may be about to meet his match.
English track: Dolby digital 5.1; DTS 5.1.
Commentary, French and Spanish tracks: Dolby digital 2.0 surround.
Special features: commentary by director Mark Steven Johnson and producer Gary Foster; theatrical trailer; text commentary; enhanced viewing mode; 6 multi-angle scene studies; "Beyond Hell's Kitchen: making Daredevil" documentary with optional enhanced viewing mode; "The men without fear: the art of Daredevil" documentary; HBO First Look special; Daredevil #1 virtual comic book; "Shadow world": an in-depth look at "Daredevil's sight"; modeling sheet; bios for your favorite heroes and villains; Kingpin featurette; 3 music videos: "Won't Back Down" by Fuel, "For You" by the the Calling, "Bring Me to Life" by Evanescence; Jennifer Garner screen test bio; still gallery; full-length screenplay.
Director of photography, Ericson Core ; editors, Dennis Virkler, Armen Minasian ; music, Graeme Revell ; costume designer, James Acheson ; production designer, Barry Chusid.
Ben Affleck, Jennifer Garner, Micheal Clarke Duncan, Colin Farrell.
MPAA rating: PG-13; for action/violence and some sensuality.
Keywords: Murdock, Matt (Fictitious character) -- Drama; Lawyers -- New York (State) -- New York -- Drama; Hell's Kitchen (New York, N.Y.) -- Drama; Superhero films; Video recordings for the hearing impaired; Feature films